Fewer culturable Lactobacillaceae species identified in faecal samples of pigs performing manipulative behaviour - König, Emilia (Springer Nature, 2025)
Manipulative behaviour that consists of touching or close contact with ears or tails of pen mates is common in pigs and can become damaging. Manipulative behaviour was analysed from video recordings of 45-day-old pigs, and 15 manipulator-control pairs (n = 30) were formed. Controls neither received nor performed manipulative behaviour. Rectal faecal samples of manipulators and controls were compared. 16S PCR was used to identify Lactobacillaceae species and 16S amplicon sequencing to determine faecal microbiota composition. Seven culturable Lactobacillaceae species were identified in control pigs and four in manipulator pigs. Manipulators (p = 0.02) and females (p = 0.005) expressed higher Lactobacillus amylovorus, and a significant interaction was seen (sex * status: p = 0.005) with this sex difference being more marked in controls. Females (p = 0.08) and manipulator pigs (p = 0.07) tended to express higher total Lactobacillaceae. A tendency for an interaction was seen in Limosilactobacillus reuteri (sex * status: p = 0.09). Results suggest a link between observed low diversity in Lactobacillaceae and the development of manipulative behaviour.